2003
DOI: 10.1177/0021934702250024
|View full text |Cite
|
Sign up to set email alerts
|

The Myths Of Oppositional Culture

Abstract: Informed by the Afrocentric quest to "abandon ethnocentric and racist systems of logic and to place the un-discussed in the center of discourse" (Asante, 1990, p. 6), this article challenges oppositional culture theory and the idea of "acting White." More specifically, this article first reveals how oppositional culture theory, at its core, is a culture-of-poverty theory of Black academic underperformance. Second, this article examines the notion of acting White and ties it to the critical literature on Whiten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Understanding the experiences of these students might have important implications for improving achievement levels and for mediating school failure among African American students. Lundy (2003) argues that rather than rejecting academic success, many black students see high achievement as cultural agency and resistance against white supremacy. Therefore, they engage rather than disengage from schools.…”
Section: Student Oppositional Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the experiences of these students might have important implications for improving achievement levels and for mediating school failure among African American students. Lundy (2003) argues that rather than rejecting academic success, many black students see high achievement as cultural agency and resistance against white supremacy. Therefore, they engage rather than disengage from schools.…”
Section: Student Oppositional Identitymentioning
confidence: 99%
“…Rather than focusing on disengagement or culture of poverty or opposition, this project emphasizes school engagement and resilience among black students. Researchers have found that rather than leveling their school aspirations, many black students engage in school and use it as a form of self and group agency (Hilliard, 2003;Lundy, 2003). This research investigates the school experiences of high achieving African American students.…”
Section: Student Oppositional Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized tests often fail to provide opportunities for poor and racially diverse students to demonstrate their advanced potential (Sternberg, 2007), may be culturally biased, often lack in quality, and do not accurately measure how or what minority or disadvantaged students have learned (Baker, 2005;Garcia & Guerra, 2004). Addressing pervasive systemic inequalities, classism, and racism that are perpetuated or reinforced in schools is ultimately more equitable than continuing to respond to test score discrepancies with increased test preparation and focus on basic skills (Armstrong, 2010;Bomer, Dworin, May, & Semingson, 2008;Boykin, 1985;Gorski, 2007Gorski, & 2008Lundy, 2003;Rogalsky, 2009). …”
Section: Systemic Factors That Contribute To Poor Fitmentioning
confidence: 99%
“…Funding in public school districts often reflects social and racial stratification (Biddle & Berliner, 2002;Condron & Roscigno, 2003), and poor and racially diverse students encounter inequities in the schooling experiences themselves (Fram, Miller-Cribbs, & Van Horn, 2007;Giroux & Schmidt, 2004;Kozol, 1991). In EFFECTIVE EDUCATIONAL PRACTICE 13 addition, the standardized tests that are common measures of student learning are often ineffective measures of culturally or racially diverse students' capabilities (Baker, 2005;Garcia & Guerra, 2004;Sternberg, 2007) and subsequently promote misguided responses, especially heavy remediation (Armstrong, 2010;Bomer, Dworin, May, & Semingson, 2008;Boykin, 1985;Gorski, 2007Gorski, & 2008Lundy, 2003;Rogalsky, 2009). …”
mentioning
confidence: 99%